The hepatic transcriptome of the turkey poult (Meleagris gallopavo) is minimally altered by high inorganic dietary selenium. - Rachel M Taylor; Kristelle M Mendoza; Juan E Abrahante; Kent M Reed; Roger A Sunde (PLoS ONE)
There is interest in supplementing animals and humans with selenium (Se) above Se-adequate levels, but the only good biomarker for toxicity is tissue Se. We targeted liver because turkeys fed 5 μg Se/g have hepatic Se concentrations 6-fold above Se-adequate (0.4 μg Se/g) levels without effects on growth or health. Our objectives were (i) to identify transcript biomarkers for high Se status, which in turn would (ii) suggest proteins and pathways used by animals to adapt to high Se. Turkey poults were fed 0, 0.025, 0.4, 0.75 and 1.0 μg Se/g diet in experiment 1, and fed 0.4, 2.0 and 5.0 μg Se/g in experiment 2, as selenite, and the full liver transcriptome determined by RNA-Seq. The major effect of Se-deficiency was to down-regulate expression of a subset of selenoprotein transcripts, with little significant effect on general transcript expression. In response to high Se intake (2 and 5 μg Se/g) relative to Se-adequate turkeys, there were only a limited number of significant differentially expressed transcripts, all with only relatively small fold-changes. No transcript showed a consistent pattern of altered expression in response to high Se intakes across the 1, 2 and 5 μg Se/g treatments, and there were no associated metabolic pathways and biological functions that were significant and consistently found with high Se supplementation. Gene set enrichment analysis also found no gene sets that were consistently altered by high-Se and supernutritional-Se. A comparison of differentially expressed transcript sets with high Se transcript sets identified in mice provided high Se (~3 μg Se/g) also failed to identify common differentially expressed transcript sets between these two species. Collectively, this study indicates that turkeys do not alter gene expression in the liver as a homeostatic mechanism to adapt to high Se.